Respostas
respondido por:
7
sistema na forma F(x)=y , levando a y=ax+b
5=a+b
-4=-2a+b
Resolvendo o sistema:
a=5-b substituindo
-4=-2(5-b)+b
-4=-10+2b
b=6/2 ...... b=3
Substituindo b:
5=a+3 .... a=2
logo substituindo a e b na forma geral: f(x)=ax+b
y=2x+3
5=a+b
-4=-2a+b
Resolvendo o sistema:
a=5-b substituindo
-4=-2(5-b)+b
-4=-10+2b
b=6/2 ...... b=3
Substituindo b:
5=a+3 .... a=2
logo substituindo a e b na forma geral: f(x)=ax+b
y=2x+3
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás